Poor agreement between endoscopists and gastrointestinal pathologists for the interpretation of probe-based confocal laser endomicroscopy findings - Peter, Shajan; Council, Leona; Bang, Ji Young; Neumann, Helmut; Moenkemueller, Klaus; Varadarajulu, Shyam; Wilcox, Charles Melbern (World Journal of Gastroenterology, 2014)
To compare the interpretation of probe-based confocal laser endomicroscopy (pCLE) findings between endoscopists and gastrointestinal (GI)-pathologists.All pCLE procedures were undertaken and the endoscopist rendered assessment. The same pCLE videos were then viewed offline by an expert GI pathologist. Histopathology was considered the gold standard for definitive diagnosis. The sensitivity, specificity and accuracy for diagnosis of dysplastic/ neoplastic GI lesions and interobserver agreement between endoscopists and experienced gastrointestinal pathologist for pCLE findings were analyzed.Of the 66 included patients, 40 (60.6%) had lesions in the esophagus, 7 (10.6%) in the stomach, 15 (22.7%) in the biliary tract, 3 (4.5%) in the ampulla and 1 (1.5%) in the colon. The overall sensitivity, specificity and accuracy for diagnosing dysplastic/neoplastic lesions using pCLE were higher for endoscopists than pathologist at 87.0% vs 69.6%, 80.0% vs 40.0% and 84.8% vs 60.6% (P = 0.0003), respectively. Area under the ROC curve (AUC) was greater for endoscopists than the pathologist (0.83 vs 0.55, P = 0.0001). Overall agreement between endoscopists and pathologist was moderate for all GI lesions (K = 0.43; 95%CI: 0.26-0.61), luminal lesions (K = 0.40; 95%CI: 0.20-0.60) and those of dysplastic/neoplastic pathology (K = 0.55; 95%CI: 0.37-0.72), the agreement was poor for benign (K = 0.13; 95%CI: -0.097-0.36) and pancreaticobiliary lesions (K = 0.19; 95%CI: -0.26-0.63).There is a wide discrepancy in the interpretation of pCLE findings between endoscopists and pathologist, particularly for benign and malignant pancreaticobiliary lesions. Further studies are needed to identify the cause of this poor agreement.
EVALuna2:1916